(untitled) (Biological Sciences - PJSIR, 2007)
. Characteristic levels of Cd, Cu, Cr, Ni, Pb, Mn and Zn in surface water and sediments from an oil impacted area in the Abalagada-Aboh catchments in the Niger Delta were studied. Except for Pb, the concentrations of dissolved or heavy metals i n the surface water were below the limits of detection. However, mean concentrations of lead in the surface water exceeded WHO limit for drin ki ng water; whereas, the concentrations of heavy metals in the natural and agricul tural soi l s sed iments were fou nd with in l imits. Th e sign ificant enrichm ent i n th e l evels of h eavy metals was due to oi l spillage and rel ated an thropogenic activi t i es. The enrich ment factor for heavy metal i n the sediment follow the order Cd > Ni > Zn > Pb > Cr > Mn > Cu. The Mehl ich Ill extractab l e metals i n the sediment ranged from 62.0-78.3% for Cd, 1.3-11.4% for Cr, 6- 1 8.0% for Cu, 14.0-51 .3% for Pb, 12.0-20% for Ni, 8.0-17.5% for Mn and 26.3-45.0% for Zn. The Mehlich Ill extractable metals follow the order: Cd > Zn > Pb > Mn > Ni > Cu > Cr which does not tally with the order of enrichment factor i ndicati ng that heavy metal enrichment of sediment does not necessary implies !ability and bioavailabi l i ty of the elements in the sediment matrix. Overall metal availabi l ity i ndicates contami nation potential risk of cadmi um, lead and zi nc i n the Abalagada-Aboh catchment.